Trio Album for violin, violoncello and piano, vol.I - ALBENIZ, I [et.al.] (The Boston Music Co.)
Tango in DnMinuetnBy the BrooknPrelude in A-flatnPassepiednSerenadenTold at TwilightnValzer gentileninterlude orientalnElegy